2005
DOI: 10.1002/bmc.547
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of haloperidol, its three metabolites and two other butyrophenone‐type neuroleptics by high performance liquid chromatography with dual ultraviolet detection

Abstract: We investigated simultaneous determination of haloperidol (HAL), its three metabolites [reduced HAL (R-HAL), 3-(4-fluorobenzoyl)propionic acid (FBPA) and 4-(4-chlorophenyl)-4-hydroxypiperidine (CPHP)] and two related compounds [spiperone (SPI) and droperidol (DRO)] in phosphate-buffered saline using high-performance liquid chromatography (HPLC) coupled with dual ultraviolet detection (220 and 250 nm). Retention times of HAL, R-HAL, FBPA, CPHP, SPI and DRO were 16.8, 11.8, 10.2, 4.1, 12.6 and 8.3 min, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Although many of the studied compounds have weakly actives metabolites [24][25][26][27], these were not included in the current study considering that their appearance in brain samples of suicide cases would be of little forensic relevance. In these cases, as discussed below, high concentrations of the parent drug are the determining factors when drawing conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Although many of the studied compounds have weakly actives metabolites [24][25][26][27], these were not included in the current study considering that their appearance in brain samples of suicide cases would be of little forensic relevance. In these cases, as discussed below, high concentrations of the parent drug are the determining factors when drawing conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that there are significantly different responses among individuals on exposure to a particular drug [2,3] due to pharmaco-kinetic [3] and pharmaco-dynamic variations.…”
Section: Introductionmentioning
confidence: 99%
“…So, for a broad and complete determination it is advantageous for the laboratory to have methods as described here that may be used for more than a single compound. At present, determination of some of these drugs has been established by high performance liquid chromatography (HPLC) with UV detection [2,[14][15][16][17][18][19][20][21], HPLC with coulometric detection [22,23] or fluorescence detection [24,25]. Although electrochemical detection [26][27][28][29][30] offers enhanced sensitivity in the low ng/ml range, electrochemical detectors require optimal working conditions, sample preparation is critical and interference from co-medications is often unavoidable.…”
Section: Introductionmentioning
confidence: 99%